Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

The steps below show the solution to the equation 3(x−2)=2(x−3). Order the reasons for the steps.


3(x−2)=2(x−3)


3(x)+3(−2)=2(x)+2(−3)

[ Select ]


3x−6=2x−6

[ Select ]


3x−2x=−6+6

[ Select ]


x=0

[ Select ]


Fill out the select options with either:


A. Addition and subtraction properties of equality

B. Distributive property

C. Add and subtract

D. Multiply


Sagot :

Answer: B, D, A, C

Step-by-step explanation:

To find the reasons for the steps, let's solve the equation.

3(x−2)=2(x−3)                          [distribute]

3(x)+3(−2)=2(x)+2(−3)             [multiply]

3x−6=2x−6                               [add and subtract both sides by 2x and -6]

3x−2x=−6+6                            [add and subtract]

x=0

Therefore, the order would be B, D, A, C.

We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.